Case Report: Activating PIK3CD Mutation in Patients Presenting With Granulomatosis With Polyangiitis - Lu, Meiping; Gu, Weizhong; Sheng, Yuanjian; Wang, Jingjing; Xu, Xuefeng (Frontiers in Immunology, 2021)
Activated phosphoinositide 3-kinase δ syndrome (APDS) is an autosomal dominant primary immunodeficiency caused by gain-of-function (GOF) mutations in PIK3CD or PIK3R1 genes. The phenotypes of APDS are highly variable, ranging from asymptomatic adults to profound immunodeficiency causing early death in childhood. Herein, we reported two pediatric patients with APDS presented with recurrent lung infections, sinusitis, hematuria, and positive anti-neutrophil cytoplasmic antibody (ANCA), previously diagnosed as granulomatosis with polyangiitis (GPA). Bronchoscopy showed mucosal nodule lymphoid hyperplasia in the entire airway. Many inflammatory cells infiltrated around the airway and in the lung parenchyma, and numbers of CD3+ T cells and CD20+ B cells were significantly increased, especially CD3+ T cells. Whole exome sequencing showed that they had the E1021K (c.3061 G >A) mutation in the PIK3CD gene. These are the first reported cases of APDS presenting as childhood-onset GPA. Pediatricians should suspect of APDS in the differential diagnosis of children who present with GPA-like symptoms. Additionally, timely and repeated bronchoscopies could contribute to providing an important diagnostic clue for APDS.